Efficacy and toxicity of PACEBOM chemotherapy in relapsed/refractory aggressive lymphoma in the rituximab era. Issue 3 (22nd December 2016) - Tamjid, Babak; Mckendrick, Joseph; Schwarer, Anthony; Doig, Rowan; James, Philip; Hosking, Patrick; Hawkes, Eliza A
Abstract: Aim: Relapsed/refractory (R/R) aggressive lymphoma outcomes are poor. There is no standard treatment. PACEBOM (prednisolone, doxorubicin, cyclophosphamide, etoposide, bleomycin, vincristine and methotrexate) has shown efficacy for several lymphoma subtypes in published reports. We evaluate PACEBOM+/–rituximab for R/R aggressive lymphomas in this millennium. Methods: In this retrospective, single‐center study, R/R aggressive lymphoma patients who received PACEBOM or its derivatives were identified from the pharmacy database. Demographic, treatment, toxicity and survival data were collected. Results: A total of 37 eligible patients were identified. Histological subtypes included 20 Diffuse Large B‐Cell Lymphoma (DLBCL), 10 T‐Cell Lymphoma (TCL) and 7 Hodgkin lymphoma. All DLBCL patients had received prior rituximab. Thirty‐one (84%) received second‐line PACEBOM. Median number of cycles was six (1–6). Eighteen out of 20 B‐cell lymphoma patients received R‐PACEBOM. Overall response rate was 65%, 70% and 71% in patients with DLBCL, TCL and Hodgkin lymphoma respectively. Thirteen patients underwent autologous stem cell transplant post‐PACEBOM. Median follow‐up was 49 months (3–201). Most common grade 3–4 toxicities were neutropenia (46%), anemia (24%) and thrombocytopenia (16%). No additional toxicity was seen in patients who received rituximab. Conclusion: In this cohort, PACEBOM is active in R/R aggressive lymphoma with manageable toxicity and can be safely combined with rituximab. Outcomes were similar to reports of other salvage regimens. PACEBOM remains a suitable option for R/R aggressive lymphoma, in patients exposed to prior rituximab and those planned for autologous stem cell transplant.